Pengembangan Kedelai Di Papua: Potensi Lahan, Strategi Pengembangan, Dan Dukungan Kebijakan - Garuda, Siti Raodah; Baliadi, Yuliantoro; Lestari, Martina S. (Jurnal Penelitian dan Pengembangan Pertanian, 2017)
ABSTRACTSoybean is one of startegies and important food crops in Indonesia. Soybean products are used for human consumption, animal feed, and a variety of non-food consumer and industrial products. They are considered a complete source of plant base protein because all of the essential amino acids are supplied. Soybean can be grown in a wide variety of soil and climate. More than 60% of Indonesiaâs soybean consumption still needs to be imported from a broad in case of Papua, about 25% soybean demands is originated from Java island. To meet the needs that important to enhance domestic soybean production. There foreadditional plantations will have to be develop outside Java island such as Papua. Papua hasmany assets favouring soybean growing. Notable Â among these are significan 2,75 million ha land area. A highly favorable climate with abundant rainfall, farmers with ample know-how, availability high yielding varieties, existing market potential and a satisfactory economic and government institutional support. In the utilization of land farmerâs need to get coaching and accompanied by an intensively both in land preparation, cultivating maintenance harvesting and post-harvesting by agricultural extension by implementing a specific technology innovation particularly good or sertified seeds of high yielding adapted soybean variety. In line with those, the strategy priorties are development of a seed sector, rehabilitation of all the site previously developed for food crops growing areas, agricultural advice, mechanization at production and technology transfer, support for processing and marketing local price.Key words : Land potential, Papua, production, soybean, strategyABSTRAKKedelai adalah salah satu tanaman pangan yang startegis dan penting di Indonesia. Produk kedelai digunakan untuk bahan pangan, pakan ternak, dan berbagai produk olahan dan produk industri. Kedelai merupakan sumber protein nabati lengkap karena semua asam amino esensial yang terkandung didalamnya. Kedelai dapat tumbuh di berbagai kondisi tanah dan iklim. Lebih dari 60% dari konsumsi kedelai di Indonesia masih perlu diimpor dari luar negeri. Di Papua, sekitar 25% kebutuhan kedelai didatangkan dari pulau Jawa. Memenuhi kebutuhan kedelai tersebut yang terpenting adalah meningkatkan produksi kedelai dalam negeri. Oleh karena itu peningkatan budidaya kedelai perlu dikembangkan di luar pulau Jawa seperti Papua. Papua memiliki potensi yang tinggi untuk pengembangan kedelai. Adanya potensi lahan sekitar 2,75 juta ha, iklim yang sangat menguntungkan dengan curah hujan yang melimpah, tingkat pengetahuan petani yang cukup, ketersediaan varietas unggul, potensi pasar yang menjanjikan, kepuasan ekonomi dan dukungan lembaga pemerintah. Dalam pemanfaatan lahan, petani membutuhkan pembinaan dan pendampingan yang intensif mulai dari persiapan lahan, penanaman, pemeliharaan, panen dan pasca panen oleh penyuluh pertanian dengan menerapkan inovasi teknologi spesifik lokasi, khususnya benih yang baik atau bersertifikat dari varietas kedelai yang memiliki adaptasi yang tinggi. Sejalan dengan itu, strategi prioritas adalah juga pengembangan melalui sektor perbenihan, perbaikan lahan pengembangan Â tanaman pangan terlantar, perluasaan areal tanam, mekanisasi produksi dan transfer teknologi untuk mendukung proses produksi dan pemasaran.Â Kata kunci : Potensi lahan, Papua, produksi, kedelai, strategi.